Barriers to HIV and sexual and reproductive health care for female sex workers in Tete, Mozambique: results from a cross-sectional survey and focus group discussions. (December 2016) - Lafort, Yves; Lessitala, Faustino; Candrinho, Balthazar; Greener, Letitia; Greener, Ross; Beksinska, Mags; Smit, Jenni; Chersich, Matthew; Delva, Wim
Abstract Background In the context of an operational research project in Tete, Mozambique, use of, and barriers to, HIV and sexual and reproductive health (HIV/SRH) commodities and services for female sex workers (FSWs) were assessed as part of a baseline situational analysis. Methods In a cross-sectional survey 311 FSWs were recruited using respondent driven sampling and interviewed face-to-face, and three focus group discussions were held with respectively 6 full-time Mozambican, 7 occasional Mozambican and 9 full-time Zimbabwean FSWs, to investigate use of, and barriers to, HIV/SRH care. Results The cross-sectional survey showed that 71 % of FSWs used non-barrier contraception, 78 % sought care for their last sexually transmitted infection episode, 51 % of HIV-negative FSWs was tested for HIV in the last 6 months, 83 % of HIV-positive FSWs were in HIV care, 55 % sought help at a health facility for their last unwanted pregnancy and 48 % after sexual assault, and none was ever screened for cervical cancer. Local public health facilities were by far the most common place where care was sought, followed by an NGO-operated clinic targeting FSWs, and places outside the Tete area. In the focus group discussions, FSWs expressed dissatisfaction with the public health services, as a result of being asked for bribes, being badly attended by some care providers, stigmatisation and breaches of confidentiality. The service most lacking was said to be termination of unwanted pregnancies. Conclusions The use of most HIV and SRH services is insufficient in this FSW population. The public health sector is the main provider, but access is hampered by several barriers. The reach of a FSW-specific NGO clinic is limited. Access to, and use of, HIV and SRH services should be improved by reducing barriers at public health facilities, broadening the range of services and expanding the reach of the targeted NGO clinic.